Characteristics of physical activity interventions and effects on cardiorespiratory fitness in children aged 6–12 years—A systematic review. Issue 3 (March 2018) - Braaksma, Petra; Stuive, Ilse; Garst, Rianne (M.E.); Wesselink, Carlijn F.; van der Sluis, Corry K.; Dekker, Rienk; Schoemaker, Marina M.
Abstract: Objectives: To examine the characteristics of physical activity (PA) interventions and the effects on cardiorespiratory fitness (CRF) in healthy children based on treatment theory. Design: Systematic review. Methods: PubMed and Embase were searched for studies published between 2003 and 2016. Inclusion criteria were: Participants: healthy children aged 6–12. Interventions: interventions with activities to increase PA behaviour or physical fitness (PF) regardless of setting. Control: no or alternative intervention. Outcome: exercise-based CRF measure with appropriate analysis of CRF effects. Study design: randomized controlled trial. Effect size was calculated using dppc2 and the methodological quality of the studies was assessed using the PEDro scale. Results: Of 1002 studies screened, 23 met the inclusion criteria. Thirteen of the 23 studies found statistically significant improvements in CRF and eight studies showed medium to high effect sizes. Interventions with medium to high effect sizes focused more often on PF than PA behaviour, had slightly higher frequencies of activities and had a shorter duration than the less effective interventions. Conclusions: The fact that thirteen studies demonstrated statistically significant improvements in CRF is promising but also emphasizes the need to keep improving research methods and the development and execution of interventions. Interventions with larger effect sizes appear to be more controlled, as they usually relied on smaller sample sizes and the components of these interventions encompassed protocolled training sessions which defined and monitored the relative training intensity intended. A duration of at least six weeks and a frequency of three to four times a week is recommended.